2004
DOI: 10.1111/j.1523-1739.2004.00538.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Systematic Reserve Selection to Decisions about Scale, Biological Data, and Targets: Case Study from Southern British Columbia

Abstract: The identification of conservation areas based on systematic reserve-selection algorithms requires decisions related to both spatial and ecological scale. These decisions may affect the distribution and number of sites considered priorities for conservation within a region. We explored the sensitivity of systematic reserve selection by altering values of three essential variables. We used a 1:20,000-scale terrestrial ecosystem map and habitat suitability data for 29 threatened vertebrate species in the Okanaga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 35 publications
4
73
0
1
Order By: Relevance
“…The index is expressed as C j = i/(a + b + i) £ 100, where i is the number of grid cells selected at both of two regional extents, a is the number of additional cells selected at the smaller regional extent but not the larger, and b is the number of additional cells selected at the larger regional extent but not the smaller. The signiWcance of minimal set spatial congruence was determined by comparing the observed Jaccard with randomly generated values, following Warman et al (2004). We generated Jaccard values for 100 pairs of randomly selected sets of sites (maintaining the same number of sites in each pair).…”
Section: Analysesmentioning
confidence: 99%
“…The index is expressed as C j = i/(a + b + i) £ 100, where i is the number of grid cells selected at both of two regional extents, a is the number of additional cells selected at the smaller regional extent but not the larger, and b is the number of additional cells selected at the larger regional extent but not the smaller. The signiWcance of minimal set spatial congruence was determined by comparing the observed Jaccard with randomly generated values, following Warman et al (2004). We generated Jaccard values for 100 pairs of randomly selected sets of sites (maintaining the same number of sites in each pair).…”
Section: Analysesmentioning
confidence: 99%
“…é impossível representar todos os componentes da biodiversidade, por isso geralmente são usadas medidas ou conjuntos parciais de dados. Devem ser atribuídos objetivos explícitos ou metas de representação numa rede de reservas a esses conjuntos para a região de interesse no processo de seleção de áreas (Pressey & logan 1998, Warman et al 2004, Justus et al 2008. Alguns exemplos de objetivos usados são populações de determinados tamanhos, um número específico de populações das espécies, uma porcentagem do total das distribuições das espécies, ou da distribuição de classes ambientais.…”
Section: Conceitos Básicos E Diferentes Abordagens Complementaridade unclassified
“…The percentage area required to conserve viable populations of the full assemblage of herbivores was 50% on average, and was consistent for all desired population sizes. As well, the percentage land required was only influenced in a limited way by the grain of the selection unit (cell size), although other studies suggest that the size of the selection unit will have an effect on the size of the area needed to conserve species (e.g., Logan 1995, 1998;Warman et al 2004). Thus, Solomon et al (2003) concluded, that for their study area, percentage targets were consistent, albeit much larger than percentage targets advocated by conservation groups.…”
Section: Introductionmentioning
confidence: 99%